Narratives of subversion the fantasy mode in Philippine contemporary fiction in English - Delgado, Daryll Jane S. (2008)
Narratives of Subversion is a study of fantasy as narrative mode. It reads a selection of Philippine contemporary novels and short stories in English that employ fantasy as a narrative mode. It explores the qualities, elements, functions and the implications of the employment of fantasy as a narrative mode. More specifically, this study looks into the ways by which fantasy, a narrative mode, operates as a mode of subversion and of questioning. In relation to this problematic, the study likewise seeks to answer the following questions: 1. What is the location of fantasy in relation to other narrative modes, both realist and non-realist, that are employed in Philippine contemporary fiction in English? 2. In what ways is fantasy a narrative mode driven by and constitutive of desire, operating within and as ideology? 3. In what ways does fantasy as a narrative mode make apparent/express, undermine, or subvert culturally [ideologically] dominant notions of subjectivity and representation? As the title suggests, this study is also an analysis of the forces and relations of fantasy-production in the texts, hence the term "fantasy mode", and hence the preoccupation with issues of configurations of desire and jouissance between Subject and the Other, as well as with other subjectifying practices seen in the texts. Thus, while the study performs a close textual analysis--that is, of the manifest text--of four novels and five collections of short stories, it also pays close attention to the texts' unconscious, understood in the study as that which is left out in the process of construction, as being structured like a language, and being a repository of desire. This study, therefore, reads the latent text; the theoretical (and ideological) structure which both frames and produces the repertoire of conflicting and contesting discourses out of which a text is materially organized. It focuses on the problematic of the text. The method of analysis employed in this study is based on the theoretical suggestions of Pierre Macherey in A Theory of Literary Production, as well as on Jacques Lacan's "The insistence of the letter in the Unconscious", which are likewise echoed in Neferti Tadiar's Fantasy-Production: Sexual Economies and other Philippine Consequences for the New World Order (2004), Slavoj Zizek's The Plague of Fantasies (1998) and Rosemary Jackson's Fantasy: The Literature of Subversion (1991). Apart from the above-mentioned critical approaches that informed this thesis, the critical discourse that frames and directs the analysis undertaken in this study proceeds from the theoretical fusion of Lacanian psychoanalysis and Althusserian Marxism, also through Catherine Belsey's Critical Practice. Fantasy as it is used in this study then refers to a narrative mode that functions, operates, or is located in between the opposing poles of the marvelous and the mimetic. This space, in which fantasy operates, is characterized as being transgressively fertile, questioning culturally dominant notions of what is real. It is likewise a location that allows for a diametrical contradiction of established a continual reversal of internally established ground-rules, going beyond a mere inversion of reality, and more towards its subversion. This study attempts to go beyond the standard notion of fantasy as a mode which obfuscates the true horror of a situation, of fantasy as escape from or mere inversion of reality. It emphasizes rather the idea of fantasy as operating within ideology (Zizek 190). Fantasy is also understood here then as "a field of symbolically structured meaning (the unconscious) that shapes and regulates our desires, our modes of acting in reality... [it] is thus not thought divorced from projects and actions" (Tadiar 9). Chapter 1 of this study expounds further on the problem of the study, provides a brief background and examples of similar analytical approaches, and discusses the theoretical assumptions and key concepts that inform this reading. Chapter 2 explores the ways by which fantasy as a narrative mode in Nick Joaquin's Cave and Shadows interrogates notions of the "real", and of the "subject", and how fantasy possibly subverts such notions in the process. More specifically, it explores how, through interpolating texts and continual reversals, fantasy, a narrative mode, is also a mode of subversion. Chapter 3 studies the workings of fantasy in historiographic metafiction texts, and examines how history figures as the object as well as means of desire in the novels Great Philippine Jungle Energy Café by Alfred Yuson and The Firewalkers by Erwin Castillo. Chapter 4 focuses on how fantasy, as a field of symbolically structured meaning, driven by desire, structures and disrupts notions of the 'real' in the novel Salamanca. This chapter likewise attempts to problematize the so-called "innocence" of the text, and explores how texts such as these can purvey dominant ideologies even as they attempt to disrupt them. Chapter 5 looks into the ways by which fantasy, as a narrative mode in urban fantasy and horror stories is driven by unconscious desire, and continually attempts to compensate for a lack resulting from cultural constraints. Chapter 6 explores how the withdrawal into a fantasy world constitutes a protest against life-denying "reality", and explores the problematic of the cost of displaying fundamental desires, in the "punk gothic" stories of Karl De Mesa. The final chapter contains a summary of the findings of the study, reiterates that the various novels and short stories illustrate how fantasy functions in diverse ways, contingent upon different ideological, political and economic determinants; and offers other possible, political implications. The primary texts taken up in this study display the following qualities of fantasy: (1) as a narrative mode that operates in the hesitation between the mimetic and the marvelous; (2) as literature of desire, which seeks that which is experienced as absence and loss; (3) as literature of subversion, indicating or pointing to the seemingly precarious foundation of order;. While this study forwards the suggestion that such qualities and functions of fantasy may also mean an opposition to a dominant ideology, this study also posits the above stated qualities and tendencies of fantasy (sustained ambiguity, going beyond mere inversion and more towards continual reversal; functioning like ideology; and constitutive of desire) are not in themselves socially subversive. They, however, disturb dominant rules of literary representation and reproduction of, at the very least, the "real", and more so the realist notion of the subject as the origin of meaning, as unitary, as whole. Moreover, as the findings of this study show, fantasy is at its most subversive, when it not only displays the construction of the subject, the castration complex, and repressed desires, but also when fantasy moves to change the relations and points of contact of the imaginary and the symbolic. In doing so, fantasy reveals the text's unconscious, the ideology at work, and also provides spaces to disrupt the work of ideology.